JUDUL ARTIKEL KEDUA - Kwon, Chang-hoon (Training Open Journal System LPPI UMS, 2018)
Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak. Ini adalah abstrak.